Curcumol alleviates endometriosis via correcting the aberrant activation of Fas/RIPK1-mediated PANoptosis - Ni, Weiming; Wu, Xiaoqin; Feng, Li; Xu, Min; Tian, Yingzhou (Frontiers in Pharmacology, 2025)
Endometriosis (EMs) is an estrogen-dependent chronic inflammatory disease. While apoptosis resistance (evidenced by Bcl-2 upregulation and Bax/caspase-3 downregulation) remains a hallmark of EMs, recent studies reveal a paradoxical coexistence of aberrant apoptotic activation (Fas/FADD/Caspase-8) and inflammatory PANoptosis in ectopic lesions, suggesting novel therapeutic targets for this complex disorder. GEO database mining revealed PANoptosis-related genes in EMs, which was experimentally validated through clinical and animal studies demonstrating the critical role of Fas/FADD/Caspase-8/RIPK1 signaling. Curcumol, the active component of Curcuma zedoaria rhizomes, exhibited strong binding affinity to Fas/RIPK1 in molecular docking and dynamics simulations, and effectively alleviated EMs progression by modulating this pathway, providing novel therapeutic insights for EMs management.